2016
DOI: 10.1177/0194599816646359
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Changes of the Peripheral Vestibular System Secondary to Chronic Otitis Media

Abstract: The findings of our study suggest that the decrease in the number of vestibular sensory cells and dark cells could be the cause of the clinical symptoms of imbalance of some patients with chronic otitis media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
4
27
0
Order By: Relevance
“…Worldwide, the incidence of acute otitis media is 10.85%, accounting for over 709 million new cases every year . It is associated with several acute complications and long‐term sequelae, which include hearing loss, delayed speech and neurologic development, tinnitus, and dizziness . In the past years, several studies have hypothesized the presence of high‐frequency hearing loss as a potential long‐term sequela of acute otitis media .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Worldwide, the incidence of acute otitis media is 10.85%, accounting for over 709 million new cases every year . It is associated with several acute complications and long‐term sequelae, which include hearing loss, delayed speech and neurologic development, tinnitus, and dizziness . In the past years, several studies have hypothesized the presence of high‐frequency hearing loss as a potential long‐term sequela of acute otitis media .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies aiming to evaluate patients who had recurrent acute otitis media or chronic otitis media with effusion using standard audiograms (250 Hz–8 kHz) failed to demonstrate significant threshold changes as compared with controls . However, studies using extended high‐frequency audiometry (8 kHz–16 kHz) reported downward threshold shifts in patients who had a history of recurrent acute otitis media.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations